Resonant neutralization of H− near Cu surfaces: Effects of the surface symmetry and ion trajectory - Chakraborty, Himadri; Niederhausen, Thomas; Thumm, Uwe (My University, 2004)
A comparative study of the resonant charge-transfer process of H− in front of plane-model Cu surfaces of symmetries (111) and (100) is performed using a two-dimensional Crank-Nicholson wave-packet propagation approach. Very different electron evolutions near the two surfaces are related to different structures of the respective band gaps and allow for the visualization of electronic interaction mechanisms. It is shown that electrons get localized near the Cu(111) surface due to the reflectivity imposed by the band gap. This enables considerable recapture by the ion. In contrast, H− is neutralized more efficiently near Cu(100), for which the surface state is embedded in the bulk valence band. Image states are found to be important intermediaries for charge transfer at smaller ion-surface distances. As a consequence of all these effects, the dynamics of ion neutralization near (111) and (100) surfaces vastly differ to yield quite dissimilar ion-survival probabilities. It is found that while the ion-surface interaction time becomes important at normal incidence, for near-grazing incidences, the point of closest approach to the surface is a crucial determinant of the ion survival.